2021
DOI: 10.1097/jcn.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Self-management Interventions for Patients With Heart Failure

Abstract: Background: Heart failure (HF) is a multifaceted syndrome that requires self-management for adherence to treatment to control symptoms. Symptoms need to be monitored to prevent impending HF exacerbations. Few HF study authors have assessed efficacy of mobile health (mHealth) interventions particularly with virtual visits to evaluate outcomes such as symptoms and healthcare utilization. Objective: The aim of this pilot study was to evaluate the potential effect of mHealth self-management interventions on sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 25 publications
(74 reference statements)
0
29
0
Order By: Relevance
“…All 28 included articles [ 38 - 65 ] were published from 2012 onward and covered 27 studies and 23 interventions (n=4, 17% interventions were evaluated in ≥1 paper, using different study designs [ 39 , 44 , 47 , 52 , 56 , 59 , 63 - 65 ]). Of the 28 studies, there were 18 (64%) experimental studies [ 38 - 55 ], (n=10, 56% RCTs [ 38 - 47 ] and n=8, 44% quasi-experimental [ 48 - 55 ]; n=7, 39% with a qualitative component [ 38 , 44 , 46 , 49 , 51 , 52 , 54 ]; Table 1 ), 9 (32%) qualitative-only studies, 5 (18%) that included interviews [ 56 - 60 ], and 4 (14%) that involved a survey with open-ended questions ( Table 2 ) [ 57 - 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 28 included articles [ 38 - 65 ] were published from 2012 onward and covered 27 studies and 23 interventions (n=4, 17% interventions were evaluated in ≥1 paper, using different study designs [ 39 , 44 , 47 , 52 , 56 , 59 , 63 - 65 ]). Of the 28 studies, there were 18 (64%) experimental studies [ 38 - 55 ], (n=10, 56% RCTs [ 38 - 47 ] and n=8, 44% quasi-experimental [ 48 - 55 ]; n=7, 39% with a qualitative component [ 38 , 44 , 46 , 49 , 51 , 52 , 54 ]; Table 1 ), 9 (32%) qualitative-only studies, 5 (18%) that included interviews [ 56 - 60 ], and 4 (14%) that involved a survey with open-ended questions ( Table 2 ) [ 57 - 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 28 studies, there were 18 (64%) experimental studies [ 38 - 55 ], (n=10, 56% RCTs [ 38 - 47 ] and n=8, 44% quasi-experimental [ 48 - 55 ]; n=7, 39% with a qualitative component [ 38 , 44 , 46 , 49 , 51 , 52 , 54 ]; Table 1 ), 9 (32%) qualitative-only studies, 5 (18%) that included interviews [ 56 - 60 ], and 4 (14%) that involved a survey with open-ended questions ( Table 2 ) [ 57 - 64 ]. Most studies were conducted in the United States (15/28, 54%) [ 39 , 40 , 44 , 45 , 48 , 50 , 52 , 54 , 56 , 58 , 60 - 64 ] and Canada (4/28, 14%) [ 47 , 51 , 55 , 59 ], and most were single-center, except for a few (5/28, 18%) [ 38 , 42 , 43 , 55 , 62 ]. There were 1397 participants (n=8-232 in experimental studies and 5-37 in qualitative studies), mean age was 63.4 years, 30% were women, 68% were White (from 15/28, 54% studies that reported on ethnicity), and the average education level was high ( Multimedia Appendix 4 [ 38 - 65 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative descriptive research creates a close description of participants' subjective experience [27,28]. Participants were recruited from the intervention groups of a larger parent study using a mobile app related to heart failure self-management [29]. The parent study was a three-group repeated measures randomized controlled pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…A brief description of the intervention will be provided in this manuscript, as a full description of the sample and study is under review in another paper [29]. The 12-week intervention promoted self-management using mHealth as a platform.…”
Section: Intervention Descriptionmentioning
confidence: 99%
“…[ 14 , 15 ] analyzed the effect of the use of wearables and apps for cardiac rehabilitation of arrhythmia patients, whereas [ 16 , 17 , 18 ] studied a series of prevention and treatment programs for heart failure management through mHealth. Additionally, in [ 2 , 19 , 20 , 21 , 22 ] the functionalities of mHealth apps for heart failure self-management were evaluated.…”
Section: Introductionmentioning
confidence: 99%